Lifelong learning idea against the background of Poles’ needs - Przybysz, Klaudia (Idea kształcenia ustawicznego na tle potrzeb Polaków, 2014)
The rate of economic changes and the aging of the population made it necessary to give priority to the importance of lifelong learning (see for example the Lisbon Strategy). The conducted study concerned the demand on courses, trainings and certifications in Poland. This article aims to analyze the educational needs reported by respondents who are in the production age. Our study contains the classification based on sex, education level, type of occupation in relation to whether respondents declare such needs. The research also included the type of courses undertaken and their assessment with respect to the usefulness for further professional life. The proposed approach to this issue may be a substructure of a multidimensional analysis of the situation on the labour market and it may help to identify the factors determining the attractiveness of potential employees from the perspective of employers’ needs.
Ekonometria = Econometrics, 2014, Nr 3 (45), s. 31-41
Keywords: lifelong learning; multidimensional analysis; labour market; wielowymiarowa analiza statystyczna; rynek pracy